Pengaruh Penambahan Sari Buah Strawberry Terhadap Kadar Vitamin C Dan Daya Terima Jelly Lidah Buaya - Amanah, Marisca; , Dwi Sarbini,SST, M.Kes (2017)
Introduction: Jelly is a semi-solid food made from fruit juice and sugar. Aloe vera is prospective to be processed into a variety of food products (food and drink) with high economic value such as jelly. The use of synthetic dyes into the body will cause effects such as cancer or other diseases. One of natural dyes is strawberry. The nutrients that are most numerous in the strawberry fruit is vitamin C. Objective: To determine the effect of strawberry juice on vitamin C and acceptability of aloe vera jelly. Methods: The study was conducted using a randomized block design with the addition of fruit juice strawberry composition varying with variations in treatment of 0%; 10%; 20%; 30%. Results: The highest vitamin C levels of aloe vera jelly amounted to 71.75 mg while the average value acceptability is 3.63. Conclusions: The study shows that there is significant influence adding strawberries juice to the acceptability and vitamin C of aloe vera jelly. Suggestion: Making of aloe vera jelly should use 30% strawberry juice because it has the highest vitamin C content. Keywords: jelly, aloe vera, strawberry, vitamin C.